Protocol for Biochemical Analysis and Structure Determination of the ZZ Domain of the E3 Ubiquitin Ligase HERC2 - Liu, Jiuyang (STAR Protoc, 2020)
Since its discovery, several ligands of the ZZ domain have been identified; however, molecular and structural information underlying binding of these ligands remains limited. Here, we describe a protocol for biochemical and structural analysis of the ZZ domain of human E3 ubiquitin ligase HERC2 (HERC2(ZZ)) and its interaction with its ligands: the N-terminal tails of histone H3 and SUMO1. This methodology could be applied for characterization of binding activities of other histone readers. For complete details on the use and execution of this protocol, please refer to Liu et al. (2020).